2021
DOI: 10.48550/arxiv.2109.12766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Refined Madelung Equations

Abstract: The Madelung equations are two equations that are equivalent to the one-body time-dependent Schrödinger equation. In this paper, the Madelung equation, whose gradient is an Euler equation, is refined by introducing interpretations of functions that are shown to depend only on the realpart of the complex-valued wavefunction. These interpretations are extensions of functions from the recently derived generalized Bernoulli equation, applicable to real-valued quantum-mechanical stationary states. In particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…. Also, the integrand of the quantum-mechanical expectation value of the kinetic energy, given by (12), is interpreted as a sum of two terms: The kinetic energy per volume ρ m u 2 /2 and the pressure p. Elsewhere [43], an extension of these interpretations are used to refine, and further develop, the Madelung equations, where the quantum potential is replaced by an additional kinetic energy term and a term involving the pressure. The main equation of the formalism reduces to the Bernoullian equation (3) for stationary states with real valued wavefunctions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. Also, the integrand of the quantum-mechanical expectation value of the kinetic energy, given by (12), is interpreted as a sum of two terms: The kinetic energy per volume ρ m u 2 /2 and the pressure p. Elsewhere [43], an extension of these interpretations are used to refine, and further develop, the Madelung equations, where the quantum potential is replaced by an additional kinetic energy term and a term involving the pressure. The main equation of the formalism reduces to the Bernoullian equation (3) for stationary states with real valued wavefunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the integrand of the quantum-mechanical expectation value of the kinetic energy is given as a sum of two terms: One term is interpreted as the kinetic energy per volume and the other one is the pressure, and the kinetic energy interpretation agrees with an interpretation given by Salesi [41]. Elsewhere [43] an extension of these interpretations are used to extend the applicability range of the Madelung equations. Also, in this paper (in section 3), it is demonstrated that for many quantum mechanical stationary states, including the hydrogen atom s states, local mass conservation is incompatible with steady-flow.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation